TOOTHBRUSH AND TOWEL HANDLING AND THEIR MICROBIAL QUALITY: THE CASE OF STUDENTS OF UNIVERSITY FOR DEVELOPMENT STUDIES, NYANKPALA CAMPUS, GHANA - Twumwaa, Hannah; Asumang, Betty; Imoro, Zarouk Abubakari; Wilson Kpordze, Stephen (African Journal of Infectious Diseases (AJID), 2020)
sought to assess how students of the University for Development Studies handle their toothbrushes and towels and the consequence of that with regards to the microbial quality of these personnel hygiene materials. Materials and Methods: A total of 100 swap samples were collected (50 toothbrushes and 50 towels) for microbial analysis. Questionnaires were administered to students from whom samples were collected to ascertain information on how they handle toothbrushes and towels. MacConkey agar and Mannitol Salt agar were used to isolate E. coli and S. aureus respectively, and cefoxitin used to identify the methicillin-resistant S. aureus strains. Results: E. coli was present in all sampled towels, while 98% of the sampled toothbrushes contained E. coli. It was found that 2% of the respondents kept their toothbrushes in bathhouses, 44% kept them unenclosed in rooms and 54% kept them enclosed in rooms (54%). Also, 48% of the respondents washed their towels once a week, 24% washed once every two weeks, 20% once every month and 8% once a trimester. Moreover, 52% dried their towels in rooms while 48% dried them outside rooms. The occurrence of S. aureus was 96% and 94% respectively for the towels and toothbrushes. Of the S. aureus isolated, 33.3% of sampled towels and 12.8% of the toothbrushes contained methicillin-resistant S. aureus. Conclusion: This study found that, students are at risk of contracting infectious disease if their personal hygiene behaviours do not changed.